2014
DOI: 10.1007/s10551-014-2170-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Leadership Styles on Employees’ Outcomes in International Luxury Hotels

Abstract: This study examines the effects of transformational, transactional, and non-transactional leadership on hotel employees' outcomes including extra effort, perceived efficiency, and satisfaction with managers. Employees from eleven 4-star hotels in Spain provided the collected data. A series of statistical analyses (1) identify the elements of three leadership styles using a multi-factor leadership questionnaire (MLQ-5X), (2) examine the effect of leadership styles on employees' outcomes. The results of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 95 publications
(105 reference statements)
3
34
1
3
Order By: Relevance
“…Therefore it is important to show fullrange leadership as Bass, Avolio, Jung, Berson (2003) suggested. This is consistent with a study by Quintana, Park, & Cabrera (2015) in which they found that both transformational and contingent reward form of leadership styles are related to participative to safety related events. In the current study, transactional leadership also found to be significantly related both of the safety outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore it is important to show fullrange leadership as Bass, Avolio, Jung, Berson (2003) suggested. This is consistent with a study by Quintana, Park, & Cabrera (2015) in which they found that both transformational and contingent reward form of leadership styles are related to participative to safety related events. In the current study, transactional leadership also found to be significantly related both of the safety outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…They emulate the values and beliefs of the leaders they idealized. Leaders who exhibit idealized behavior influence their followers; in return, followers emulate the behavior (Quintana, Park, & Cabrera, 2015). Transformational leaders are visionary, trusted, and respected (Avolio, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Followers identify with transformational leader's vision, which makes it easier to accomplish common goals. An idealized behavior is often identified as the force that motivates followers to be creative (Quintana et al, 2015). Idealized leaders empower employees to be creative and accomplish organizational goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al [26] found in their study that transformational leadership has a positive effect on organisational justice and job characteristics. It is found that employees outperform the targets if leaders with transformational leadership can set the goal with clear communication and can motivate them [27]. Employees find self-respect and put additional efforts to achieve the goals if they are challenged and if the goals are set at high levels [28].…”
Section: Literature Reviewmentioning
confidence: 99%